The effect of replacement of wheat bran by graded levels of molasses on digestion, degradation and digestion kinetics of fibre and rumen digesta pool size in crossbred (Bos taurus X Bos indicus) steers fed native grass hay - Khalili, H.; Osuji, P.O. (Elsevier, 1994)
This paper evaluates the effect of replacement of wheat bran by graded levels of sugar cane molasses on digestibility, degradation of fibre, digestion kinetics of fibre and rumen pool sizes. Four ruminally fistulated crossbred steers were given a basal diet of grass hay ad libitum and wheat bran. The other three diets consisted of replacement of wheat bran with molasses. Urea was used to make the three diets isonitrogenous with the basal diet. Intake and digestibility of neutral detergent fibre decreased with increasing levels of molasses. Similarly neutral detergent fibre (NDF) digestion expressed as a proportion of potentially digestible NDF decreased linearly when the level of molasses increased. The disappearance of hay DM from nylon bags decreased with increasing wheat bran substitution by molasses. The disappearance of NDF of hay dry matter (DM) from nylon baghs decreased with increasing wheat bran substitution by molasses. The disappearance of NDF of hay from nylon bags decreased significantly only at 48h and at 96h when the amount of molasses increased. Although there were differences between diets in rumen pool sizes of DM, NDF and in digestion Kinetics of NDF, these were not, in general, explained by polynomial orthogonal contrasts. Increasing the level of molasses caused a clear linear effect only for rate of digestion of NDF and true rate of digestion of NDF. There was also a quadratic effect for rate of passage of indigestible NDF, showing that diets ML and MM had greater rate of passage compared with the other two diets when the level of molasses was increased.